IDNLearn.com offers expert insights and community wisdom to answer your queries. Join our interactive community and get comprehensive, reliable answers to all your questions.
Sagot :
To solve for [tex]\((f - g)(x)\)[/tex] given the functions [tex]\(f(x) = x^2 + 1\)[/tex] and [tex]\(g(x) = 5 - x\)[/tex], we should first derive the function [tex]\((f - g)(x)\)[/tex].
Step-by-Step Solution:
1. Define the Functions:
[tex]\[ f(x) = x^2 + 1 \][/tex]
[tex]\[ g(x) = 5 - x \][/tex]
2. Compute [tex]\((f - g)(x)\)[/tex]:
[tex]\[ (f - g)(x) = f(x) - g(x) \][/tex]
Substitute the given functions:
[tex]\[ (f - g)(x) = (x^2 + 1) - (5 - x) \][/tex]
3. Simplify the Expression:
[tex]\[ (f - g)(x) = x^2 + 1 - 5 + x \][/tex]
[tex]\[ (f - g)(x) = x^2 + x - 4 \][/tex]
Next, we need to evaluate [tex]\((f - g)(x)\)[/tex] for various values. Let's initially evaluate it for [tex]\(x\)[/tex] in the range of integers from [tex]\(-10\)[/tex] to [tex]\(10\)[/tex]:
[tex]\[ \begin{aligned} & \text{For } x = -10: & (f - g)(-10) &= (-10)^2 + (-10) - 4 = 100 - 10 - 4 = 86 \\ & \text{For } x = -9: & (f - g)(-9) &= (-9)^2 + (-9) - 4 = 81 - 9 - 4 = 68 \\ & \text{For } x = -8: & (f - g)(-8) &= (-8)^2 + (-8) - 4 = 64 - 8 - 4 = 52 \\ & \text{For } x = -7: & (f - g)(-7) &= (-7)^2 + (-7) - 4 = 49 - 7 - 4 = 38 \\ & \text{For } x = -6: & (f - g)(-6) &= (-6)^2 + (-6) - 4 = 36 - 6 - 4 = 26 \\ & \text{For } x = -5: & (f - g)(-5) &= (-5)^2 + (-5) - 4 = 25 - 5 - 4 = 16 \\ & \text{For } x = -4: & (f - g)(-4) &= (-4)^2 + (-4) - 4 = 16 - 4 - 4 = 8 \\ & \text{For } x = -3: & (f - g)(-3) &= (-3)^2 + (-3) - 4 = 9 - 3 - 4 = 2 \\ & \text{For } x = -2: & (f - g)(-2) &= (-2)^2 + (-2) - 4 = 4 - 2 - 4 = -2 \\ & \text{For } x = -1: & (f - g)(-1) &= (-1)^2 + (-1) - 4 = 1 - 1 - 4 = -4 \\ & \text{For } x = 0: & (f - g)(0) &= (0)^2 + (0) - 4 = 0 + 0 - 4 = -4 \\ & \text{For } x = 1: & (f - g)(1) &= (1)^2 + (1) - 4 = 1 + 1 - 4 = -2 \\ & \text{For } x = 2: & (f - g)(2) &= (2)^2 + (2) - 4 = 4 + 2 - 4 = 2 \\ & \text{For } x = 3: & (f - g)(3) &= (3)^2 + (3) - 4 = 9 + 3 - 4 = 8 \\ & \text{For } x = 4: & (f - g)(4) &= (4)^2 + (4) - 4 = 16 + 4 - 4 = 16 \\ & \text{For } x = 5: & (f - g)(5) &= (5)^2 + (5) - 4 = 25 + 5 - 4 = 26 \\ & \text{For } x = 6: & (f - g)(6) &= (6)^2 + (6) - 4 = 36 + 6 - 4 = 38 \\ & \text{For } x = 7: & (f - g)(7) &= (7)^2 + (7) - 4 = 49 + 7 - 4 = 52 \\ & \text{For } x = 8: & (f - g)(8) &= (8)^2 + (8) - 4 = 64 + 8 - 4 = 68 \\ & \text{For } x = 9: & (f - g)(9) &= (9)^2 + (9) - 4 = 81 + 9 - 4 = 86 \\ & \text{For } x = 10: & (f - g)(10) &= (10)^2 + (10) - 4 = 100 + 10 - 4 = 106 \\ \end{aligned} \][/tex]
So, the results for [tex]\((f - g)(x)\)[/tex] from [tex]\(x = -10\)[/tex] to [tex]\(x = 10\)[/tex] are:
[tex]\[ [(-10, 86), (-9, 68), (-8, 52), (-7, 38), (-6, 26), (-5, 16), (-4, 8), (-3, 2), (-2, -2), (-1, -4), (0, -4), (1, -2), (2, 2), (3, 8), (4, 16), (5, 26), (6, 38), (7, 52), (8, 68), (9, 86), (10, 106)] \][/tex]
This comprehensive evaluation list provides the values of [tex]\((f - g)(x)\)[/tex] for [tex]\(x\)[/tex] from [tex]\(-10\)[/tex] to [tex]\(10\)[/tex].
Step-by-Step Solution:
1. Define the Functions:
[tex]\[ f(x) = x^2 + 1 \][/tex]
[tex]\[ g(x) = 5 - x \][/tex]
2. Compute [tex]\((f - g)(x)\)[/tex]:
[tex]\[ (f - g)(x) = f(x) - g(x) \][/tex]
Substitute the given functions:
[tex]\[ (f - g)(x) = (x^2 + 1) - (5 - x) \][/tex]
3. Simplify the Expression:
[tex]\[ (f - g)(x) = x^2 + 1 - 5 + x \][/tex]
[tex]\[ (f - g)(x) = x^2 + x - 4 \][/tex]
Next, we need to evaluate [tex]\((f - g)(x)\)[/tex] for various values. Let's initially evaluate it for [tex]\(x\)[/tex] in the range of integers from [tex]\(-10\)[/tex] to [tex]\(10\)[/tex]:
[tex]\[ \begin{aligned} & \text{For } x = -10: & (f - g)(-10) &= (-10)^2 + (-10) - 4 = 100 - 10 - 4 = 86 \\ & \text{For } x = -9: & (f - g)(-9) &= (-9)^2 + (-9) - 4 = 81 - 9 - 4 = 68 \\ & \text{For } x = -8: & (f - g)(-8) &= (-8)^2 + (-8) - 4 = 64 - 8 - 4 = 52 \\ & \text{For } x = -7: & (f - g)(-7) &= (-7)^2 + (-7) - 4 = 49 - 7 - 4 = 38 \\ & \text{For } x = -6: & (f - g)(-6) &= (-6)^2 + (-6) - 4 = 36 - 6 - 4 = 26 \\ & \text{For } x = -5: & (f - g)(-5) &= (-5)^2 + (-5) - 4 = 25 - 5 - 4 = 16 \\ & \text{For } x = -4: & (f - g)(-4) &= (-4)^2 + (-4) - 4 = 16 - 4 - 4 = 8 \\ & \text{For } x = -3: & (f - g)(-3) &= (-3)^2 + (-3) - 4 = 9 - 3 - 4 = 2 \\ & \text{For } x = -2: & (f - g)(-2) &= (-2)^2 + (-2) - 4 = 4 - 2 - 4 = -2 \\ & \text{For } x = -1: & (f - g)(-1) &= (-1)^2 + (-1) - 4 = 1 - 1 - 4 = -4 \\ & \text{For } x = 0: & (f - g)(0) &= (0)^2 + (0) - 4 = 0 + 0 - 4 = -4 \\ & \text{For } x = 1: & (f - g)(1) &= (1)^2 + (1) - 4 = 1 + 1 - 4 = -2 \\ & \text{For } x = 2: & (f - g)(2) &= (2)^2 + (2) - 4 = 4 + 2 - 4 = 2 \\ & \text{For } x = 3: & (f - g)(3) &= (3)^2 + (3) - 4 = 9 + 3 - 4 = 8 \\ & \text{For } x = 4: & (f - g)(4) &= (4)^2 + (4) - 4 = 16 + 4 - 4 = 16 \\ & \text{For } x = 5: & (f - g)(5) &= (5)^2 + (5) - 4 = 25 + 5 - 4 = 26 \\ & \text{For } x = 6: & (f - g)(6) &= (6)^2 + (6) - 4 = 36 + 6 - 4 = 38 \\ & \text{For } x = 7: & (f - g)(7) &= (7)^2 + (7) - 4 = 49 + 7 - 4 = 52 \\ & \text{For } x = 8: & (f - g)(8) &= (8)^2 + (8) - 4 = 64 + 8 - 4 = 68 \\ & \text{For } x = 9: & (f - g)(9) &= (9)^2 + (9) - 4 = 81 + 9 - 4 = 86 \\ & \text{For } x = 10: & (f - g)(10) &= (10)^2 + (10) - 4 = 100 + 10 - 4 = 106 \\ \end{aligned} \][/tex]
So, the results for [tex]\((f - g)(x)\)[/tex] from [tex]\(x = -10\)[/tex] to [tex]\(x = 10\)[/tex] are:
[tex]\[ [(-10, 86), (-9, 68), (-8, 52), (-7, 38), (-6, 26), (-5, 16), (-4, 8), (-3, 2), (-2, -2), (-1, -4), (0, -4), (1, -2), (2, 2), (3, 8), (4, 16), (5, 26), (6, 38), (7, 52), (8, 68), (9, 86), (10, 106)] \][/tex]
This comprehensive evaluation list provides the values of [tex]\((f - g)(x)\)[/tex] for [tex]\(x\)[/tex] from [tex]\(-10\)[/tex] to [tex]\(10\)[/tex].
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com provides the answers you need. Thank you for visiting, and see you next time for more valuable insights.